Obama’s America: Why it is likely to endure in Asia - Deepak Nair (2016)
Two key underlying themes have predicated the discourses on Barack Obama’s visit to Asia. First, the US has weakened. Second, Asia has changed substantially. But contrary to conclusions of “irrevocable decline”, America still has an enduring role in Asia.